Ischemic Stroke Rate Increases in Young Adults: Evidence for a Generational Effect? - Joel N. Swerdel; George G. Rhoads; Jerry Q. Cheng; Nora M. Cosgrove; Abel E. Moreyra; John B. Kostis; William J. Kostis (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
Background The incidence rates of ischemic stroke and ST‐segment elevation myocardial infarction (STEMI) have decreased significantly in the United States since 1950. However, there is evidence of flattening of this trend or increasing rates for stroke in patients younger than 50 years. The objective of this study was to examine the changes in incidence rates of stroke and STEMI using an age‐period‐cohort model with statewide data from New Jersey. Methods and Results We obtained stroke and STEMI data for the years 1995–2014 from the Myocardial Infarction Data Acquisition System, a database of hospital discharges in New Jersey. Rates by age for the time periods 1994–1999, 2000–2004, 2005–2009, and 2010–2014 were obtained using census estimates as denominators for each age group and period. The rate of stroke more than doubled in patients aged 35 to 39 years from 1995–1999 to 2010–2014 (rate ratio [RR], 2.47; 95% CI, 2.07–2.96 [P<0.0001]). We also found increased rates of stroke in those aged 40 to 44, 45 to 49, and 50 to 54 years. Strokes rates in those older than 55 years decreased during these time periods. Those born from 1945–1954 had lower age‐adjusted rates of stroke than those born both in the prior 20 years and in the following 20 years. STEMI rates, in contrast, decreased in all age groups and in each successive birth cohort. Conclusions There appears to be a significant birth cohort effect in the risk of stroke, where patients born from 1945–1954 have lower age‐adjusted rates of stroke compared with those born in earlier and later years.